Bioactivity of Inhaled Methane and Interactions With Other Biological Gases - Juhász, László; Tallósy, Szabolcs Péter; Nászai, Anna; Varga, Gabriella; Érces, Dániel; Boros, Mihály (Frontiers in Cell and Developmental Biology, 2022)
A number of studies have demonstrated explicit bioactivity for exogenous methane (CH4), even though it is conventionally considered as physiologically inert. Other reports cited in this review have demonstrated that inhaled, normoxic air-CH4 mixtures can modulate the in vivo pathways involved in oxidative and nitrosative stress responses and key events of mitochondrial respiration and apoptosis. The overview is divided into two parts, the first being devoted to a brief review of the effects of biologically important gases in the context of hypoxia, while the second part deals with CH4 bioactivity. Finally, the consequence of exogenous, normoxic CH4 administration is discussed under experimental hypoxia- or ischaemia-linked conditions and in interactions between CH4 and other biological gases, with a special emphasis on its versatile effects demonstrated in pulmonary pathologies.